Implementasi Model Kooperatif STAD dalam Pembelajaran IPS - Soni Amrulloh, Muhammad; Kurniawan, Khoiruzzaim; Muhammad Sajjad, Arsyad (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
The learning model is essentially implemented based on the needs experienced by the students. The application of the cooperative learning model, specifically the STAD type, can ease a teacher in carrying out the process. This research aims to explore the implementation of the STAD-type cooperative learning model in Social Studies (IPS) subjects at MTs Al-Islam Joresan. The research method used is descriptive qualitative, focusing on the application of the STAD-type cooperative learning model in the Social Studies (IPS) subject at MTs Al-Islam Joresan. The results of the study show that the implementation of the STAD-type cooperative learning model in the Social Studies (IPS) subject at MTs Al-Islam Joresan is very easy to apply. Secondly, the benefits of implementing this model are numerous, including training collaboration, improving understanding, increasing learning motivation, fostering interaction, and practicing speaking skills during presentations